1982
DOI: 10.1021/j100220a029
|View full text |Cite
|
Sign up to set email alerts
|

Gas-chromatographic study of the solution thermodynamics of hydroxylic derivatives and related compounds

Abstract: under contract No. F33615-78-C-2075, and by the Division of Chemical Sciences, Office of Basic Energy Sciences, U.S. Department of Energy, under contract W-7405-eng-26 with the Union Carbide Corp. M.S. is grateful for financial assistance from Norges Teknisk-Naturvitenskapelige Forskningsrád. We note with thanks the technical assistance of J. Cobb and D. Goff, and helpful advice from J. Brynestad and C. A. Angelí.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 7 publications
1
58
0
Order By: Relevance
“…The Flory-Huggins interaction parameter represents the size-corrected free energy of solution and is calculated as RT. 10 The enthalpy of solution is calculated based on eq. (2) as…”
mentioning
confidence: 99%
“…The Flory-Huggins interaction parameter represents the size-corrected free energy of solution and is calculated as RT. 10 The enthalpy of solution is calculated based on eq. (2) as…”
mentioning
confidence: 99%
“…This increase was more important for aromatic compounds and was supposedly caused by the increase in the electronic density, and hence the polarity, of the aromatic compounds. Activity coefficients at infinite dilution for squalane were less than one; these low values suggest low solution enthalpies for the methyl-alkane interactions, as found by Langer et al (1982). It can also be observed that this value increased as the size of solute increased.…”
Section: Resultsmentioning
confidence: 57%
“…12,13 For some solutes, data were not measured for 80°C because of lengthy retention time; for these, high-temperature data 36,37 were used to obtain ∆H h e ∞ and ∆S h re ∞ , and results were adjusted to 90°C using eq 3. The slopes and correlation coefficients (R) of S vs H , and vs H plots were determined and results are shown in Table 2.…”
Section: Solute State Interactionsmentioning
confidence: 99%